Use of the anaerobic speed reserve to normalize the prescription of high-intensity interval exercise intensity - Julio, U. F.; Panissa, V. L. G.; Paludo, A. C.; Alves, E. D.; Campos, F. A. D.; Franchini, E. (European Journal of Sport Science, 2020)
The aim of this study was to compare the perceptual and physiological responses and time-to-exhaustion in high intensity interval exercise (HIIE) protocols that are prescribed based on the relative anaerobic speed reserve (ASR) or maximal aerobic speed (MAS) in athletes with different ASR values, as well as the coefficient of variation (CV) of the abovementioned variables. Eleven long-distance runners and ten rugby players were submitted to five experimental sessions on different days; the first and second session were intended for the determination of the anthropometry, MAS and maximal sprint (MSS). In the subsequent sessions, three HIIE15:15s protocols were performed until exhaustion (110%MAS, ?25%ASR, and ?50%ASR) in random order. The anthropometric characteristics and variables obtained from the MAS and MSS tests in the different groups were compared by Student`s unpaired t-test. The analysis of mixed models for repeated measures (groups and protocols) was used to compare the speed, delta blood lactate, rating of perceived exertion, and time-to-exhaustion. Rugby players presented higher ASR (13.6 ± 0.9 km h-1) compared to long-distance runners (12.6 ± 0.9 km h-1) (P = .049). For the HIIE15:15s protocols, there were no protocol and group interaction effects. However, lower CV values were observed for time-to-exhaustion (a mean reduction of 52%) and delta blood lactate (a mean reduction of 48%) in Delta25%ASR and Delta50%ASR when compared to 110%MAS. Furthermore, the rating of perceived exertion CV was similar in all HIIE15:15s protocols. The prescription of intensity of HIIE based on the ASR was able to reduce the inter-subject variability of lactate and time-to-exhaustion in rugby players and long-distance runners.